2014
DOI: 10.3109/02770903.2014.927482
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral anatomical changes in female asthma patients with and without depression compared to healthy controls and patients with depression

Abstract: Current findings provided convergent evidence to support the critical role of the right STG in the brain mechanism that mediates asthma and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…This could lead to further activity limitations and non-adherence to medicines, which then results in poor asthma outcomes. Furthermore, in our recently published magnetic resonance imaging and voxel-based morphometry study, we reported structural changes in the right superior temporal gyrus in female asthma patients with depression, and reduced gray matter volume in the right superior temporal gyrus was associated with increased airway hyperresponsiveness (34). This suggests that the right superior temporal gyrus may play a critical role in the link between asthma and depression.…”
Section: Discussionmentioning
confidence: 79%
“…This could lead to further activity limitations and non-adherence to medicines, which then results in poor asthma outcomes. Furthermore, in our recently published magnetic resonance imaging and voxel-based morphometry study, we reported structural changes in the right superior temporal gyrus in female asthma patients with depression, and reduced gray matter volume in the right superior temporal gyrus was associated with increased airway hyperresponsiveness (34). This suggests that the right superior temporal gyrus may play a critical role in the link between asthma and depression.…”
Section: Discussionmentioning
confidence: 79%
“…The inflammatory response associated with atopic diseases is thought to affect the neurocircuitry including those involved in speech [ 172 , 173 ]. Markedly, adults with asthma show atypical gray [e.g., increased gray matter volume in the right superior temporal gyrus; 174 ], and white [e.g., lower white matter coherence in the inferior frontal gyrus; 175 ] matter in regions involved in speech production and reported to be affected in stuttering [ 176 ]. Although the mechanism of causality is unclear, the relationship between atopic diseases and stuttering, suggests that research on the impact of childhood health outcomes and stuttering is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…56 The mechanisms responsible for depression worsening asthma outcomes are not clearly established, and may relate to inflammation, cerebral anatomic changes, autonomic nervous dysfunction, decreased adherence, or ineffective self-management behaviors. 57…”
Section: Unique Factors That Can Complicate Asthma Management Among Omentioning
confidence: 99%